Sequence–lithofacies paleogeographic evolution and its control on deep and ultra–deep reservoir types: A case study of the Permian Maokou Formation in northeastern Sichuan Basin - Xiandong Wang; Wancang Tan; Peng Lu; Ying Wang; Qiang Li; Liang Zhao; Pengfei Niu; Zhengyi Cang; Bao Gong; Jiagang Shen (PLoS ONE, 2025)
The Middle Permian Maokou Formation in northeastern Sichuan Basin has been explored with continuous breakthroughs in recent years, but its sequence–lithofacies paleogeographic characteristics and tectonic–sedimentary evolution process are still unclear. Based on outcrops, well logging and seismic data, this paper focuses on the sequence stratigraphic, lithofacies paleogeography and tectonic–sedimentary evolution of the Maokou Formation in northeastern Sichuan Basin. The results show that two third-order sequences (SQ1, SQ2) are developed in the Middle Permian Maokou Formation. SQ1 can be divided into three fourth-order sequences (SQ1–1, SQ1–2, and SQ1–3). SQ1–1 and SQ1–2 are generally carbonate ramps, SQ1–3 turns to rimmed carbonate platform, and its stratigraphic thickness and sedimentary facies are distributed in NW–SE direction. The succession development of carbonate platform in SQ2 sedimentary period. It is believed that, due to the NE–trending extensional stress generated by the continuous subduction of the Mianlue Ocean and the regional sea level eustacy, the Permian tectonic–sedimentary differentiation in the northeastern Sichuan Basin had begun from the early stage of the Middle Permian and gradually intensified. As a result, the platform–basin dominated deep-water deposits gradually expanded into the basin along SW–NE direction, and evolved into the features of “platform in the south and platform–basin in the north” at the end of the Maokou Formation deposition. As such, large-scale high-energy shoals are developed above the platform region during the SQ1–3 and SQ2 depositional periods, making it a prospect of conventional gas. Potential source rocks are developed in the platform-basin region, which is a potential prospect of unconventional oil and gas. The results suggest that the tectonic–sedimentary differentiation induced by the continuous subduction of Mianlue Ocean makes the Maokou Formation an ideal reservoir for both conventional and unconventional hydrocarbon.